Design and Development of a Web-Based Information System for Monitoring Mandatory Employee Training Using Firebase (Case Study: Pelni Hospital) - Wafi Hidayat Ahadi; Rizal Rizal (Technema: Journal of Intelligent Engineering and Computing, 2026)
Hospitals are required to ensure that medical and non-medical personnel maintain valid competencies through periodic mandatory training to support patient safety and accreditation compliance. PT RS PELNI still relied on manual documentation of employee training and certification records, making it difficult to monitor compliance status, identify certificates approaching expiration, and obtain centralized information for managerial decision-making. This study aimed to design and develop the Mandatory Training Monitoring Information System (SIMON), a web-based application for managing employee data, mandatory training categories, training histories, and real-time certification monitoring. The system was developed using a Research and Development (R&D) approach with the Waterfall software development model, while HTML5, CSS3, and vanilla JavaScript were employed for the front-end and Firebase Authentication together with Cloud Firestore served as the back-end infrastructure. Functional validation was conducted using Black Box Testing to evaluate the performance of all system modules. The results demonstrated that user authentication, employee management, training management, training history recording, and dashboard monitoring operated successfully according to predefined functional requirements. The implementation of Firebase enabled real-time data synchronization, allowing certificate status to be updated instantly without manual intervention. The proposed system improves administrative efficiency, supports timely monitoring of employee training compliance, and provides a scalable cloud-based solution for competency management in healthcare organizations.